THE IDENTIFICATION OF ROAD CONDITION USING SMARTPHONE ROADROID APPLICATION BASED ON CORRELATION METHOD (CASE STUDY: BYPASS LOMBOK INTERNATIONAL AIRPORT) - Kukuh Pratama; Muhammad Zainul Arifin; Achmad Wicaksono (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
A road is a land transportation infrastructure that plays an important role in regional development. Road feasibility assesses through road roughness. The purpose of this study is to assess the condition of road roughness based on the ASTM E 950-94. The technology used is a correlation-method-based Smartphone application called Roadroid. There were several types of data obtained, namely spatial data in the form of maps, visual data in the form of photos and videos, and numerical data in the form of IRI (International Roughness Index) values. Based on numerical data analysis, the indicated IRI values ranged from 2,01 to 2,13. These results represented that the Lombok International Airport Bypass road condition is currently in good and moderate condition.